The Relevance of Ki Hajar Dewantara's Thoughts in the Implementation of the Merdeka Curriculum - Jaya, Arim Irsyadulloh Albin (Yayasan Pendidikan Bustanul Ulum Mojokerto, 2025)
This study aims to analyze the relevance of Ki Hajar Dewantara's thoughts in the implementation of the Merdeka Curriculum in Indonesia. As a national education figure, Ki Hajar Dewantara emphasized education that is liberating, culture-based, and student-centered. These principles serve as an essential foundation for the Merdeka Curriculum, which aims to provide flexibility in learning while fostering students' character development and independence. One key identification in this study is the lack of explicit research connecting Ki Hajar Dewantara’s educational philosophy with the implementation of the Merdeka Curriculum. While there have been numerous studies on both subjects separately, research that directly explores the relationship between Ki Hajar Dewantara’s educational concepts and the Merdeka Curriculum remains limited. Additionally, challenges persist in the implementation of the Merdeka Curriculum, particularly in terms of educators' readiness and the adaptation of learning methods that emphasize freedom of thought. This study employs a qualitative approach with a literature review method. Data were collected through an analysis of various primary and secondary sources, including Ki Hajar Dewantara's writings, government policies related to the Merdeka Curriculum, and previous research. The analysis was conducted using a descriptive-critical approach to identify the alignment between Ki Hajar Dewantara's philosophy and the Merdeka Curriculum concept. The findings of this study indicate that the principles of ing ngarso sung tulodo, ing madyo mangun karso, tut wuri handayani, and Ki Hajar Dewantara’s concept of independent learning are highly relevant to the implementation of the Merdeka Curriculum. The results of this research can serve as a guideline for educators and policymakers in developing a more adaptive, contextual, and character-based education system in line with national education values.